Evaluation of Automated Finger Compression for Capillary Refill Time Measurement in Pediatrics - Nickel, Amanda J; Jiang, Shen; Napolitano, Natalie; Donoghue, Aaron; Nadkarni, Vinay M; Nishisaki, Akira (Pediatric emergency care, 2024)
Early shock reversal is crucial to improve patient outcomes. Capillary refill time (CRT) is clinically important to identify and monitor shock in children but has issues with inconsistency. To minimize inconsistency, we evaluated a CRT monitoring system using an automated compression device. Our objective was to determine proper compression pressure in children. Clinician force for CRT was collected during manual CRT measurement as a reference for automated compression in a previous study (12.9 N, 95% confidence interval, 12.5-13.4; n = 454). An automated compression device with a soft inflation bladder was fitted with a force sensor. We evaluated the effectiveness of the automated pressure to eliminate pulsatile blood flow from the distal phalange. Median and variance of CRT analysis at each pressure was compared. A comparison of pressures at 300 to 500 mm Hg on a simulated finger yielded a force of 5 to 10 N, and these pressures were subsequently used for automated compression for CRT. Automated compression was tested in 44 subjects (median age, 33 months; interquartile range [IQR], 14-56 months). At interim analysis of 17 subjects, there was significant difference in the waveform with residual pulsatile blood flow (9/50: 18% at 300 mm Hg, 5/50:10% at 400 mm Hg, 0/51: 0% at 500 mm Hg, P = 0.008). With subsequent enrollment of 27 subjects at 400 and 500 mm Hg, none had residual pulsatile blood flow. There was no difference in the CRT: median 1.8 (IQR, 1.06-2.875) in 400 mm Hg vs median 1.87 (IQR, 1.25-2.8325) in 500 mm Hg, P = 0.81. The variance of CRT was significantly larger in 400 mm Hg: 2.99 in 400 mm Hg vs. 1.35 in 500 mm Hg, P = 0.02, Levene's test. Intraclass correlation coefficient for automated CRT was 0.56 at 400 mm Hg and 0.78 at 500 mm Hg. Using clinician CRT measurement data, we determined either 400 or 500 mm Hg is an appropriate pressure for automated CRT, although 500 mm Hg demonstrates superior consistency.